(untitled) (INTERNATIONAL JOURNAL OF CONSTRUCTION ENGINEERING (IJCE), 2020)
In Prefabrication, the advance productions of standardized components of building are ready for quick assembling and erecting at the building site. The production of units is undertaken at factory away from the actual site i.e. the industrial method of house construction is the most suitable technique for mass production of houses. Building of any height can be constructed and blocks of houses can be erected in any geological and climate condition. Adoption of prefabrication technique and use of non-traditional technologies solve the problem to a great extent by achieving speed in construction and limiting the use of scarce material. Fly ash bricks replace burnt bricks which constitute 22% of the cost of the building.